Study enabling the use of information and communication technology to improve the performance of extension work in lattakia governorate - اسماعيل روز; عمر فاروسي (Latakia University Journal -Biological Sciences Series, 2023)
The study aimed to identify the extent to which workers in the extension units use the components of information and communication technology, and it also aimed to study the obstacles that prevent the use of information and communication technology in the extension work. Likert and chi-square test to measure the relationship between dependent and independent variables. The study reached the following results: The majority of workers in the extension units did not receive a single training course, in addition to the weak level of information infrastructure in the extension units, as well as the low level of knowledge and use of the respondents for the components of informatics in the field of agricultural extension work. As for the obstacles that hinder the empowerment of informatics in agricultural extension, the majority the respondents agree that administrative obstacles occupied the first place, followed by financial obstacles.